An Error Analysis In Writing Report Text Made ByStudents Of 9th Grade In Smp N 1 Gatak 2015/2016 Academic Year - Demastuti, Sagitha Litany, Prof. Dr. Endang Fauziati, M. Hum (2016)
This study aims to find out the most common type of errors made by students of 9 grade in writing report text. Specifically this research is : (1) to identify the type of errors in writing report text made by students of 9th grade in SMP N 1 Gatak 2015/2016 academic year, (2) to identify the types of morphological errors, syntactical errors, (3) to describe the sources of errors. The type of this research is dscriptive qualitative research. In collecting data, the researcher uses eliciation tehnique. The are three steps to collect the data, namely: firstly, the researcher entered the classroom and ask the students to write their own reprort text, secondly, the researcher collected the studets‟ works, then reads and analyzes the data by marking the types of errors which occur in the students‟ writing. Lastly, the researcher documented the data of error then classifies them based on linguistic category and surface strategy. In analyzing the data, the researcher uses the theory of James for classifying the errors, and uses Brown‟s theory for sources of the errors. The results of this study show that the reseacher found in the type of "Morphological " consist of 64 errors or 43,54 % of errors. Then in the "Syntactical" found 9 type of errors consist 55 errors or 37,41 % of errors. "Discourse" consist 28 errors or 19,05 % of errors. Key words: errors analysis, report text, source of errors, linguistic category, surface strategy